Dolina Baruna pod Makalujem (8465 m) - Kunaver, Jurij (Geografski obzornik, 2025)
The article reflects the impressions and experiences of the writter, who in 1972 participated as a geomorphologist in the 4th Yugoslav Alpinist Himalayan Expedition to Makalu. There is little data on changes in the economy, but more on the living standards of the population and the modernization of transport connections. Roads and modern bridges are slowly but steadily reaching rural areas, while access to the Barun Valley is still only possible via traditional trails. Former expedition routes are now also used by an increasing number of pilgrims and trekking hikers.
Keywords: access conditions; Arun (dolina); Arun Valley; Barun (dolina); Barun Valley; buddhism; budizem; dostopnost; geomorfologija; geomorphology; Himalaja; Makalu; Nepal; prilgrimages; romanja